The sigmoidostomy as a determining factor in the change of cutaneous bacterial colonization - Valdemir José Alegre Salles; Gustavo Simões de Araújo Alegre Salles; Isabela Simões de Araújo Alegre Salles; Julia Nicioli; Juliana Almeida Lopes (Open Journal of Bacteriology - Peertechz Publications, 2021)
Aims: Identifying the alterations occurred in the bacteriology of the dermic layer of the abdominal wall in patients who underwent a colostomy, through the qualitative and quantitative determination of the pericolostomic colonization.  Methods: 19 cases have been carried out in the sigmoid colon. As for the age range, we have observed that the average age was 52 years. All patients have been colostomized for more than seven weeks. Results: The aerobic bacterium more often found was the Escherichia coli. Among the anaerobic bacteria, the most frequent one was the Bacteroides spp (44.5%), in the benign colorectal condition, and the Peptococcus spp (43.7%) in the malign colorectal neoplasic condition. In the study of the association made between the presence of microorganism and the kind of medical condition, the Enterobacter spp bacterium had a higher incidence in the malign colorectal condition. The quantitative study showed variable rates in the number of colonies and microorganisms per gram of tissue, which is compatible with the qualitative analysis.  Conclusions: There is an alteration in the bacterial colonization in the dermic area in the pericolostomic region, as a result from the colonization of this area by bacteria present in the intestinal matter.